The effect of digital literacy levels of sports sciences faculty students on e-learning attitude - Fikret Soyer; Nuri Berk Gungor; Alptug Soyer (Ozlem Book Center, 2023)
The aim of this research is to determine the effect of digital literacy level of individuals studying at the Faculty of Sport Sciences on their e-learning attitude. The study group of the research consists of a total of 203 participants studying at the Faculty of Sport Sciences of a public university in the 2021-2022 academic year. The research was based on the relational screening model. Personal information form and Digital Literacy and Attitude Scales towards E-Learning were used as data collection tools in the study. In the process of data analysis, Parametric tests were used as a result of the data set meeting the normal distribution parameters. When the research results are examined; It can be stated that the digital literacy levels of the participants are slightly above the average and their e-learning attitudes are at an average level. It was determined that the e-learning attitude and digital literacy levels did not differ statistically according to the gender variable, and according to the athlete license variable, the e-learning attitudes of the participants were higher in favor of those with a license. Another finding obtained from the research is that the digital literacy feature has the power to explain the e-learning attitude by 17%. Therefore, it can be stated that the digital literacy feature is also important in order to improve the e-learning attitude of individuals.